2010
DOI: 10.1186/1471-2199-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of the human DHRS4 gene cluster and a proposed mechanism for its transcriptional regulation

Abstract: BackgroundThe human DHRS4 gene cluster consists of three genes, DHRS4, DHRS4L2 and DHRS4L1. Among them, DHRS4 encodes NADP(H)-dependent retinol dehydrogenase/reductase. In a previous study, we investigated the alternative splicing of DHRS4 and DHRS4L2. DHRS4L1 was added to the gene cluster recently, but little is known about its structure and expression. To reveal the regulatory mechanism of the DHRS4 gene cluster expression, we studied the structure and transcription of DHRS4L1 in the context of the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Another candidate gene dehydrogenase/reductase 4 like 2 (DHRS4L2) is located in the deletion region of 14q11.2 and is a member of the short-chain dehydrogenases/reductases family. DHRS4L2 produces multiple transcript variants through alternative splicing (55,56). The encoded protein may be an NADPH dependent retinol oxidoreductase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another candidate gene dehydrogenase/reductase 4 like 2 (DHRS4L2) is located in the deletion region of 14q11.2 and is a member of the short-chain dehydrogenases/reductases family. DHRS4L2 produces multiple transcript variants through alternative splicing (55,56). The encoded protein may be an NADPH dependent retinol oxidoreductase.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded protein may be an NADPH dependent retinol oxidoreductase. Genomic loss of DHRS4L2 may lead to low expression and has been demonstrated to be associated with risk of diseases (56,57). The DHRS4L2 gene has not yet been reported to be involved in cancer and could be considered a novel candidate gene for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of genes are alternatively spliced to express multiple proteins to increase the proteomic complexity, correlating with physiological function (Maniatis and Tasic, 2002;Modrek et al, 2001;Neverov et al, 2005), cell differentiation (Terenzi et al, 2009;Valenzuela et al, 2004), and certain diseases of human body (Tazi et al, 2009). We have previously reported that alternatively spliced RNAs are common in the posttranscriptional processing of DHRS4, DHRS4L2, and DHRS4L1, which comprise the human DHRS4 gene cluster (Du et al, 2004;Song et al, 2007;Su et al, 2010;Zhang et al, 2009a), while only one spliced variant protein, NRDRB1, of the DHRS4 gene was identified in human cervical squamous carcinoma tissues and HeLa cells. NRDRB1 has a complete deletion of exon 3, and is considered associated with cervical tumorigenesis (Song et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Total RNA was extracted from the mouse, chimpanzee, and human cell lines and prepared as described in a previous study (Su et al, 2010). In short, the RNA was extracted using TRIzol ® reagent (Invitrogen) and reverse-transcribed with a QuantiTect Reverse Transcription kit (Qiagen, Venlo, Netherlands).…”
Section: Rna Extraction and Rt-qpcrmentioning
confidence: 99%
“…Mammals such as mice, pigs, and members of the Canis family possess only one copy of the DHRS4 gene, while the chimpanzee genome harbors both the DHRS4 gene and its copy DHRS4L1. On the other hand, humans express a DHRS4 gene cluster comprising three homologous genes: DHRS4, DHRS4L2, and DHRS4L1 (Su et al, 2010). The copied DHRS4 gene cluster is arranged in tandem in chromosome 14 of the chimpanzee and human genome.…”
Section: Introductionmentioning
confidence: 99%